Bibliometric analysis of research hotspots and trends on the relationship between the gut microbiota and depression from 2020 to 2024 - Xu, Dingwen; Wu, Jijun; Lu, Zhihua; Zhao, Xu; Feng, Yang; Zhang, Weicai; Jiang, Shenglu; Zhang, Lingling; Wang, Ting; Zhao, Zhenxiong (Frontiers in Microbiology, 2024)
discussion or summary of the latest advancements and trends in this field.We retrieved research articles focused on gut microbiota and depression through the WOS database from 2020 to 2024, employing visual text analysis tools such as Citespace and VOSviewer.The literature on the relationship between gut microbiota and depression surged from 396 papers in 2020 to 711 by 2024. During this period, the journal with the highest publication rate was Nutrients. China led the countries in contributions, while University College Cork topped the institutions. Kenji Hashimoto emerged as the most prolific author. The most cited paper was authored by Cryan JF et al., published in 2019 in Physiol Rev. The keywords "gut microbiota," "depression," and "anxiety" appeared most frequently, while recent years saw explosive increases in terms like "growth performance," "receptors," "depression-like phenotypes," "stress response," "gastrointestinal symptoms," "reliability," and "neurogenesis."Our article displayed the overview of the relationship between the gut microbiome and depression from 2020 to 2024 using bibliometric methods, providing perspectives and research hotspots for studies exploring the correlation between the gut microbiome and depression.